Exemption of a joint stock company from the obligation to provide information to a shareholder - Andrey V. Gabov (Правоприменение, 2020)
The subject of research. Issues concerning the exercise of the right of shareholders to receive information are analyzed. The focus is on the issues of exemption of a joint-stock company from providing information. The development of the institute of the information provision to shareholders by joint stock companies are consistently analyzed. The main trends in the development of this institute are shown: gradually narrowing the ability of shareholders to exercise their right to receive information through such means as restriction, differentiation and exemption from providing information. Special emphasis is placed on the institute of exemption from providing information.The purpose of the article is to show the main drawbacks of the existing model of exemption of a joint-stock company from the obligation to provide information to shareholders and to formulate directions for the development of legislation. The author's main scientific hypothesis can be summarized as follows. The Federal law «On joint-stock companies» contained an initial defect in the description of information exchange between a shareholder and a joint-stock company. The shareholder's right to information was not described, in fact, it was «embedded» in the obligation of the joint-stock company to provide information. The subsequent changes to the law resulted in a narrowing of the rights of the shareholder, practically depriving the minority shareholder of the right to information. This defect has led to significant legal uncertainty when the joint-stock company exercises its right to be exempt from providing information. This uncertainty should be eliminated, because the regulatory goals for granting joint-stock companies an exemption from the obligation to provide information to shareholders (article 92.2 of the Federal law «On joint-stock companies» that counters sanctions pressure) are absolutely correct. At the same time, some of the grounds for exemption from the obligation to provide information to shareholders (article 92.1 of the Federal law «On joint-stock companies») must either be excluded or reformulated. The author notes the complete «break» between the current regulation and the ideas about information exchange between a shareholder and a joint-stock company, that initially inspired the creation of the law on joint-stock companies. The inclusion of sanctions in the law on joint - stock companies as a factor affecting the performance by a joint-stock company of its obligation to provide information to shareholders should be fully welcomed. However, the legal and technical design of the corresponding political and legal idea cannot be considered optimal. In this part, the legislation requires a complete renovation based on the principle of balancing constitutional values and the interests of the state, majority and minority shareholders.Description of research methodology. The research is based on a systematic analysis, as well as the interpretation of Russian legislation and doctrine.Information about the main scientific results. The development of legislation on joint-stock companies in terms of providing information is shown. It is shown that if legislator taking into account sanctions when regulating the obligation of a joint-stock company to provide information, the goals of legislative regulation fully comply with constitutional principles, but specific legal decisions cannot be considered optimal. Conclusions. It is concluded that development of legislation on joint-stock companies has led to a significant restriction of the ability of shareholders to receive information. The author formulated the priority of regulatory goals in countering sanctions pressure and offered specific directions for improving legal regulation.